THE PROBLEMS AND THE SOLUTIONS IN THE SUBTITLING PROCESS USING SUBTITLE WORKSHOP APPLICATION: PROJECT-BASED RESEARCH - Tambunsaribu, Gunawan (Universitas Muhammadiyah Lampung, 2026)
This study aims to identify common technical and linguistic challenges and demonstrate practical strategies for addressing them in audiovisual translation training. The research adopts a project-based approach grounded in constructivist and experiential learning theories, which emphasize learning through practical experience and problem-solving. The research employs a project-based methodology, grounded in theoretical frameworks such as constructivism and experiential learning, which emphasize the importance of hands-on, real-world problem-solving. The research is conducted with students from the English Study Program at Universitas Kristen Indonesia, aiming to explore the steps involved in creating subtitles and identify common challenges encountered in the process. Through a combination of field notes and individual interviews, the study examines the technical and linguistic issues students face, such as synchronization, timing, translation accuracy, and the adaptation of cultural references. The research also presents practical solutions for overcoming these challenges, such as adjusting timing, improving translation strategies, and using available tools for better synchronization. This research contributes to enhancing subtitling practices and provides useful recommendations for educators and professionals working in the field of audiovisual translation.Keywords: subtitling process, subtitle workshop, project-based methodology, translation accuracy, synchronization